Hemodynamic assessment in children after cardiac surgery: A pilot study on the value of infrared thermography - Bridier, Armelle; Shcherbakova, Monisha; Kawaguchi, Atsushi; Poirier, Nancy; Said, Carla; Noumeir, Rita; Jouvet, Philippe (Frontiers in Pediatrics, 2023)
INTRODUCTION: Low cardiac output syndrome in the postoperative period after cardiac surgery leads to an increase in tissue oxygen extraction, assessed by the oxygen extraction ratio. Measurement of the oxygen extraction ratio requires blood gases to be taken. However, the temperature of the skin and various parts of the body is a direct result of blood flow distribution and can be monitored using infrared thermography. Thus, we conducted a prospective clinical study to evaluate the correlation between the thermal gradient obtained by infrared thermography and the oxygen extraction ratio in children at risk for low cardiac output after cardiac surgery. METHODS: Children aged 0 to 18 years, having undergone cardiac surgery with cardio-pulmonary bypass in a pediatric intensive care unit were included in the study. One to 4 thermal photos were taken per patient using the FLIR One Pro thermal imaging camera. The thermal gradient between the central temperature of the inner canthus of the eye and the peripheral temperature was compared to the concomitant oxygen extraction ratio calculated from blood gases. RESULTS: 41 patients were included with a median age of 6 months (IQR 3-48) with median Risk Adjustment for Congenital Heart Surgery-1 score was 2 (IQR 2-3). Eighty nine thermal photos were analyzed. The median thermal gradient was 2.5°C (IQR 1,01- 4.04). The median oxygen extraction ratio was 35% (IQR 26-42). Nine patients had an oxygen extraction ratio  50%. A significant but weak correlation was found between the thermal gradient and the oxygen extraction ratio (Spearman’s test ⍴= 0.25, p = 0.016). Thermal gradient was not correlated with any other clinical or biologic markers of low cardiac output. Only young age was an independent factor associated with an increase in the thermal gradient. CONCLUSION: In this pilot study, which included mainly children without severe cardiac output decrease, a significant but weak correlation between thermal gradient by infrared thermography and oxygen extraction ratio after pediatric cardiac surgery was observed. Infrared thermography is a promising non-invasive technology that could be included in multimodal monitoring of postoperative cardiac surgery patients. However, a clinical trial including more severe children is needed.